PENGARUH IMPLEMENTASI PROGRAM AKSELERASI TERHADAP MOTIVASI BELAJAR SISWA DI SMA NEGERI 2 SUNGAI PENUH (IKIP PGRI Jember, 2017)
This study aims to reveal: (1) the implementation of the accelerated program, (2) identify and describe the student's motivation on sosiology subjects, and (3) determine the extent of accelerated learning program to improve students' motivation. This research was motivated by the phenomenon on the ground that there are different levels of students' ability to learn, so that sparked the Government to make an accelerated learning program for gifted children. This research is descriptive. Data collection tool that is used in the form of a questionnaire Likert scale models that have been tested for validity and reliability.. Based on data analysis found that: (1) the implementation of the accelerated program obtained the level of achievement of 80.54%. (2) The students' motivation level of achievement gained by 80.69%. (3) and there is a significant influence on the implementation of the accelerated learning program student motivation with a regression coefficient of 0.354. It can be concluded that the implementation of the accelerated learning program has a significant influence on student motivation. Therefore it is necessary to increase, completeness and accuracy of the factors that, in order to program accelerated learning and increased student motivation and become more